"TO SPEAK AS OTHERS SPEAK": PRIVILEGED AND "VULGAR" VOICES IN EVELINA, BY FRANCES BURNEY. Issue 1 (2nd January 2016) - Davidson, Christina
ABSTRACT: In 1783, James Beattie wrote that "to speak as others speak" was crucial for social concord. The eighteenth century witnessed a move towards standardization of language, and a growing consensus about rules of conversation, governed by context. Yet towards the end of the century, there developed an aesthetic which privileged naturalness and sincerity over artifice and imitation. This created a conundrum, for how could everyone "speak as others speak" without some form of imitation? And it raised the question of whose speech practices should establish a central variety and a mainstream way of interacting. Further, what should such a variety and speech code signify? The novelist Frances Burney engaged with such issues. In Burney's fiction, standard language and natural, polite discourse signify morally grounded characters, whose dialogue correlates with the narrative voices. However, as Burney's first novel, Evelina, or, The History of a Young Lady's Entrance into the World (1778), demonstrates, although her work can be seen to be linguistically conservative, it uses such correlations to create alternative hierarchies, based on moral rather than social evaluations. This dissolving of moral and linguistic boundaries between speakers critiques representatives of the social elite and the use they make of their power, drawing attention to the insidious, corrupting influence they have over those who emulate them.